Regulation of Tumor Immune Surveillance and Tumor Immune Subversion by TGF-β - Park, Hae-Young (The Korean Association of Immunologists, 2009)
Transforming growth factor-β (TGF-β) is a highly pleiotropic cytokine playing pivotal roles in immune regulation. TGF-β facilitates tumor cell survival and metastasis by targeting multiple cellular components. Focusing on its immunosuppressive functions, TGF-β antagonists have been employed for cancer treatment to enhance tumor immunity. TGF-β antagonists exert anti-tumor effects through #1 activating effector cells such as NK cells and cytotoxic CD8(+) T cells (CTLs), #2 inhibiting regulatory/suppressor cell populations, #3 making tumor cells visible to immune cells, #4 inhibiting the production of tumor growth factors. This review focuses on the effect of TGF-β on T cells, which are differentiated into effector T cells or newly identified tumor-supporting T cells.